The Impact of Infrastructure on Nitrate Concentration in Groundwater – A Comparative Study in the City of Sabratha (Comprehensive Journal of Science, 2025)
The energy sector of Libya is dealing with an increase in demand and severe weather conditions that Groundwater is a critical resource for both human consumption and agricultural productivity, particularly in regions facing surface water scarcity. This study investigates the relationship between urban infrastructure and nitrate contamination in groundwater in Sabratha, Libya, where inadequate sewage systems are prevalent. Through a comparative analysis of two distinct areas—one reliant on septic systems (Area A) and the other with a municipal sewage network (Area B)—this research assesses nitrate concentrations alongside related indicators such as ammonia levels and total dissolved solids. Results reveal that Area A exhibited significantly higher mean nitrate levels (51.3 mg/L) compared to Area B (34.6 mg/L), with many wells in Area A exceeding national safety standards. The findings highlight the critical role of functional wastewater infrastructure in mitigating groundwater pollution and underscore urgent recommendations for infrastructure rehabilitation, phased removal of septic systems, and enhanced groundwater monitoring. This study provides essential insights for effective water resource management and public health protection in Libya.
Keywords: groundwater, nitrite, nitrate, sewage water.